A negative electrode material and battery

By adopting a double-layer clad structure in the silicon negative electrode material of lithium-ion batteries, using carbon material and metal nanoparticle filler, combining the structure of carbon layer and metal nanowires, the problem of volume expansion of the silicon negative electrode material during charging and discharging is solved, and the cycle stability of the battery and the first-time Coulomb efficiency are improved.

CN119092690BActive Publication Date: 2025-03-07BTR NEW MATERIAL GRP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411381905.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The volume expansion of the silicon negative electrode material in lithium-ion batteries during charging and discharging is high, resulting in rapid attenuation of cracks, powdering and battery capacity, and limited circulation and rate performance.

Method used

The negative electrode material adopts a double-layer clad structure, with a core of silicon material and filler (carbon material and metal nanoparticles). The first layer includes a carbon layer and metal nanowires. The second layer is distributed on part of the surface of the first layer. The surface of the silicon material and the second layer are connected through metal nanowires to enhance electron and ion transmission efficiency.

Benefits of technology

The volume expansion performance of the negative electrode material is significantly improved, cycle stability and first-time Coulomb efficiency are improved, and powder conductivity and rate performance are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119092690B_ABST
    Figure CN119092690B_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode material and a battery, wherein the negative electrode material comprises a core and a coating layer located on at least part of the surface of the core, wherein the core comprises a silicon material and a filler, wherein the filler is distributed in the silicon material, wherein the filler comprises a carbon material and metal nanoparticles, and wherein the coating layer comprises a first layer and a second layer arranged in sequence, wherein the first layer is distributed on at least part of the surface of the core, wherein the first layer comprises a carbon layer and metal nanowires distributed on the carbon layer; and the second layer is distributed on at least part of the surface of the first layer. The negative electrode material provided by the present application can effectively inhibit the volume expansion of silicon, while improving the electron transmission efficiency and ion transmission efficiency of the negative electrode material, and improving the cycle retention rate of the negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to a negative electrode material and a battery. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their advantages such as high energy density, high output power, long cycle life and low environmental pollution.

[0003] In order to improve the energy density of batteries, the research and development of silicon negative electrode materials are becoming more mature. During the charge and discharge process of silicon negative electrode materials, silicon will undergo an alloying reaction, and the volume expansion will be as high as 400%, which will cause cracks in the silicon negative electrode material until it pulverizes and falls off, causing the battery capacity to decay rapidly. In addition, the conductivity of silicon negative electrode materials is low, resulting in limited cycle performance and rate performance. Porous silicon is generally used to improve the volume expansion of silicon, but the pore structure inside silicon will extend the ion transmission path and reduce the battery's charge and discharge efficiency. In addition, more pores will also increase the specific surface area of ​​the negative electrode material, aggravate the side reactions between the negative electrode material and the electrolyte, and cause the first coulomb efficiency of the negative electrode material to decrease and the battery capacity to decay.

[0004] Based on this, there is an urgent need to develop a negative electrode material that has high initial efficiency, excellent cycle stability and low expansion performance. Summary of the invention

[0005] The present application proposes a negative electrode material and a battery, so that the negative electrode material has high initial efficiency, excellent cycle stability and low expansion performance.

[0006] In a first aspect, the present application provides a negative electrode material, comprising a core and a coating layer located on at least a portion of the surface of the core, wherein the core comprises a silicon material and a filler, wherein the filler is distributed in the silicon material, wherein the filler comprises a carbon material and metal nanoparticles, and wherein the coating layer comprises a first layer and a second layer arranged in sequence, wherein the first layer is distributed on at least a portion of the surface of the core, wherein the first layer comprises a carbon layer and metal nanowires distributed on the carbon layer; and the second layer is distributed on at least a portion of the surface of the first layer.

[0007] In some embodiments, at least a portion of the metal nanowires extend from the surface of the silicon material into the carbon layer.

[0008] In some embodiments, at least a portion of the metal nanowires extend from the surface of the silicon material into the second layer, and the metal nanowires connect the surface of the silicon material and the second layer. In some embodiments, the material of the metal nanoparticles and the metal nanowires includes at least one of copper and silver or an alloy of the two.

[0009] In some embodiments, the average particle size of the metal nanoparticles is 1 nm to 10 nm.

[0010] In some embodiments, the mass percentage of the metal nanoparticles in the negative electrode material is 0.1% to 1.0%.

[0011] In some embodiments, the mass percentage of the metal nanowires in the negative electrode material is 1.0% to 3.5%.

[0012] In some embodiments, the average length of the metal nanowires is 100 nm to 400 nm.

[0013] In some embodiments, the metal nanowires have an average diameter of 2 nm to 10 nm.

[0014] In some embodiments, the thickness of the first layer is 50 nm to 500 nm.

[0015] In some embodiments, the thickness of the second layer is 50 nm to 100 nm.

[0016] In some embodiments, the material of the second layer includes at least one of a carbon material, a polymer, a metal oxide, and a phosphate.

[0017] In some embodiments, the polymer includes at least one of polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polydopamine, xanthan gum, polypyrrole, polythiophene, polyphenylene vinylene, polyaniline, polyacetylene, and tannic acid.

[0018] In some embodiments, the carbon material includes at least one of an amorphous carbon material and a graphitized carbon material.

[0019] In some embodiments, the metal oxide includes at least one of oxides of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn.

[0020] In some embodiments, the phosphate includes at least one of magnesium phosphate, calcium phosphate, aluminum phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate.

[0021] In some embodiments, the specific surface area of ​​the negative electrode material is 2 m 2 / g ~20 m 2 / g.

[0022] In some embodiments, the compaction density of the negative electrode material is 1.0 g / cm 3 ~1.8 g / cm 3 .

[0023] In some embodiments, the powder conductivity of the negative electrode material is 0.5 S / cm~5 S / cm.

[0024] In some embodiments, the mass percentage of carbon element in the negative electrode material is 19% to 39%.

[0025] In some embodiments, the mass percentage of silicon in the negative electrode material is 60% to 80%;

[0026] In some embodiments, the gas generation value of the negative electrode material is ≤15 mL / kg / day.

[0027] In a second aspect, the present application provides a battery, comprising the negative electrode material.

[0028] The technical solution of the present application has at least the following beneficial effects:

[0029] First, the negative electrode material provided by the present application has a coating layer on the surface of the silicon material in the negative electrode material, and the coating layer includes a first layer and a second layer arranged in sequence, and the double-layer coating effect can greatly improve the volume expansion of the negative electrode material. In addition, a filler is provided in the silicon material, and the filler includes a carbon material and metal nanoparticles. The carbon material doped with metal nanoparticles can enhance the electronic conductivity inside the silicon material, which is beneficial to the transmission of electrons during the charge and discharge process, and the carbon material distributed in the silicon material can also play a buffering role, buffering the stress of the volume expansion of the silicon material. The first layer located on the surface of the silicon material includes a carbon layer and a metal nanowire. The metal nanowire can enhance the mechanical strength of the carbon layer, thereby enhancing the particle structure strength of the negative electrode material. The metal nanowire has good ductility and electronic conductivity, and can improve the electronic transmission efficiency and ion transmission efficiency between the silicon material and the coating layer. The double-layer coating can also reduce the direct contact between the electrolyte and the silicon material, reduce the occurrence of side reactions between the silicon material and the electrolyte, so that the negative electrode material can have a higher powder conductivity, while improving the cycle performance and the first coulomb efficiency of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 A schematic diagram of the structure of the negative electrode material provided in this embodiment;

[0031] Figure 2 A schematic diagram of the process flow of the method for preparing the negative electrode material provided in this embodiment;

[0032] Figure 3 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0033] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0034] First, Figure 1 A schematic diagram of the structure of the negative electrode material provided in this embodiment, such as Figure 1 As shown, the present application provides a negative electrode material, including a core and a coating layer located on at least a portion of the surface of the core, the core including a silicon material 10 and a filler, the filler distributed in the silicon material 10, the filler including a carbon material 11 and metal nanoparticles 12, the coating layer including a first layer 20 and a second layer 30 arranged in sequence, the first layer 20 being distributed on at least a portion of the surface of the core, the first layer 20 including a carbon layer and metal nanowires 21 distributed on the carbon layer; the second layer 30 is distributed on at least a portion of the surface of the first layer.

[0035] In the above technical solution, a coating layer is arranged on the surface of the silicon material in the negative electrode material, and the coating layer includes a first layer and a second layer arranged in sequence, and the double-layer coating effect can greatly improve the volume expansion of the negative electrode material. In addition, a filler is arranged in the silicon material, and the filler includes a carbon material and metal nanoparticles. The carbon material doped with metal nanoparticles can enhance the electronic conductivity inside the silicon material, which is beneficial to the transmission of electrons during the charging and discharging process, and the carbon material distributed in the silicon material can also play a buffering role, buffering the stress of the volume expansion of the silicon material. The first layer located on the surface of the silicon material includes a carbon layer and a metal nanowire. The metal nanowire can enhance the mechanical strength of the carbon layer, thereby enhancing the particle structure strength of the negative electrode material. The metal nanowire has good ductility and electronic conductivity, and can improve the electronic transmission efficiency and ion transmission efficiency between the silicon material and the coating layer. The double-layer coating layer can also reduce the direct contact between the electrolyte and the silicon material, reduce the occurrence of side reactions between the silicon material and the electrolyte, so that the negative electrode material can have a higher powder conductivity, while improving the cycle performance and the first coulomb efficiency of the negative electrode material.

[0036] In some embodiments, the negative electrode material has a core-shell structure, and the core is the silicon material 10 .

[0037] In some embodiments, the silicon material is a primary particle, and has pores inside the silicon material.

[0038] In some embodiments, the pores of the silicon material include macropores and mesopores. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), pores with a pore diameter of more than 50 nm are called macropores, and pores with a pore diameter of 2 nm to 50 nm are called mesopores.

[0039] In some embodiments, the average pore size of the pores is 10 nm to 30 nm, indicating that most of the pores are mesopores. The three-dimensional pores distributed in the silicon material can alleviate the volume expansion of silicon during lithium insertion and provide internal expansion space for the lithiation reaction.

[0040] In some embodiments, the average particle size of the silicon material is 1 μm to 15 μm, and may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 11 μm, 13 μm, 14 μm or 15 μm, etc., which is not limited here.

[0041] In some embodiments, the porosity of the silicon material is 20% to 60%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc., which are not limited here. The suitable porosity of the silicon material can buffer the volume expansion of the silicon material during the lithium insertion process.

[0042] In some embodiments, the specific surface area of ​​the silicon material is 5 m 2 / g~400 m 2 / g, specifically 5 m 2 / g, 8m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 30m 2 / g, 50m 2 / g, 80m 2 / g、100m 2 / g, 200m 2 / g or 400m 2 / g, etc., which are not limited here. The main reason why the specific surface area of ​​silicon materials is relatively large is that silicon materials have abundant pores. When the carbon material doped with metal nanoparticles is filled into the pores of the silicon material and forms a carbon layer and a coating layer, the specific surface area of ​​the silicon material of the composite carbon material can be significantly reduced, thereby reducing the direct contact between the silicon material and the electrolyte and reducing the occurrence of side reactions.

[0043] In some embodiments, the compacted density of the silicon material is 0.8 g / cm 3 ~1.5g / cm 3 , specifically 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3or 1.5g / cm 3 Etc., no limitation is made here.

[0044] In some embodiments, the tap density of the silicon material is 0.5 g / cm 3 ~ 0.8g / cm 3 , specifically 0.5g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75 g / cm 3 , 0.79g / cm 3 , 0.8g / cm 3 Etc., no limitation is made here.

[0045] In some embodiments, the volume ratio of mesopores to macropores is (1-10): 1; specifically, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., which are not limited here. It can be understood that by controlling the volume proportion of macropores in the pore structure, the pores of the silicon material are mainly mesopores with smaller pore diameters, which can alleviate the volume expansion during the lithium insertion process and provide space for internal expansion for lithiation.

[0046] In some embodiments, the first layer 20 includes a carbon layer and metal nanowires 21 distributed in the carbon layer, and the carbon layer includes amorphous carbon.

[0047] In some embodiments, the metal nanowires 21 extend from the surface of the silicon material 10 to the carbon layer. It can be understood that the metal nanowires extend from the surface of the silicon material to the carbon layer, and the metal nanowires are staggered in the carbon layer, which can improve the mechanical strength and electronic conductivity of the carbon layer, thereby inhibiting the volume expansion of the silicon material and reducing the particle breakage and pulverization of the negative electrode material.

[0048] In some embodiments, at least part of the metal nanowires 21 extend from the surface of the silicon material into the second layer 20, and the metal nanowires 21 connect the surface of the silicon material and the second layer 30. It can be understood that the metal nanowires extend from the surface of the silicon material to the second layer in a direction away from the surface of the silicon material 10, and the metal nanowires 21 connect the silicon material 10 and the second layer 30, so that the electronic conductivity between the silicon material and the coating layer can be enhanced by the metal nanowires, thereby improving the powder conductivity of the negative electrode material.

[0049] In some embodiments, the material of the metal nanoparticles and the metal nanowires includes at least one of copper and silver or an alloy of both.

[0050] In some embodiments, the average particle size of the metal nanoparticles is 1 nm to 10 nm, specifically 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, etc., and of course, other values ​​within the above range may also be used, which are not limited here. In the present application, the average particle size of the metal nanoparticles is observed by field emission scanning electron microscopy or transmission electron microscopy, and the particle sizes of 5-10 metal nanoparticles are directly measured by a scale to take the average value of the particle sizes.

[0051] In some embodiments, the shape of the metal nanoparticles can be flake-shaped, dot-shaped, spherical, ellipsoidal, etc., which is not limited here.

[0052] In some embodiments, the mass percentage of metal nanoparticles in the negative electrode material is 0.1%~1.0%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.0%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0053] In some embodiments, the mass percentage of metal nanowires in the negative electrode material is 1.0% to 3.5%, specifically 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 3.0% or 3.5%, etc., and of course it can also be other values ​​within the above range, which is not limited here.

[0054] In some embodiments, the average length of the metal nanowires is 100 nm to 400 nm, specifically 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm, etc., and of course, other values ​​within the above range are also possible, which are not limited here. Preferably, the average length of the metal nanowires is 200 nm to 400 nm.

[0055] In some embodiments, the average diameter of the metal nanowires is 2 nm to 10 nm, and can be specifically 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 8 nm, 9 nm or 10 nm, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0056] In the present application, the average length and average diameter of the metal nanowires are observed by field emission scanning electron microscopy or transmission electron microscopy. The length and diameter of 5-10 metal nanowires are directly measured by a scale, and the average value of the length and diameter is taken.

[0057] In some embodiments, the thickness of the first layer is 50nm~500nm, specifically 50nm, 60nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm or 500nm, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The thickness of the first layer is controlled within the above range, which can reduce the side reaction between the negative electrode material and the electrolyte and improve the first coulombic efficiency and cycle performance of the negative electrode material. In order to improve the electronic conductivity of the negative electrode material, preferably, the thickness of the first layer is 50nm~100nm.

[0058] In some embodiments, the thickness of the second layer is 50nm~100nm, specifically 50nm, 60nm, 70nm, 80nm, 90nm, 95nm or 100nm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. It can be understood that the second layer can reduce the occurrence of solid-liquid interface side reactions between the negative electrode material and the electrolyte. Controlling the thickness of the second layer within the above range is beneficial to maintaining the stability of the particle structure of the negative electrode material during the cycle, can reduce the exposed Si on the surface of the negative electrode material, reduce the exposed silicon and cause a large amount of SEI to be generated during the charge and discharge process, and improve the specific capacity and electrochemical performance of the negative electrode material.

[0059] In some embodiments, the material of the second layer includes at least one of carbon material, polymer, metal oxide and phosphate. Preferably, the material of the second layer includes carbon material, that is, the first layer and the second layer are both formed of carbon material, which is conducive to reducing the impedance between the interfaces of different materials.

[0060] It can be understood that a double-layer coating is constructed on the surface of the silicon material, and the double-layer coating can further alleviate the volume expansion of the negative electrode material; the use of a double-layer coating to synergistically modify the silicon material can effectively alleviate the volume expansion of the silicon material, ensuring that the negative electrode material still has excellent electrical contact performance after lithium insertion. The coating can also effectively reduce the side reactions between the silicon material and the electrolyte, while enhancing the structural stability of the negative electrode material.

[0061] In some embodiments, the polymer includes at least one of polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polydopamine, xanthan gum, polypyrrole, polythiophene, polyphenylene vinylene, polyaniline, polyacetylene, and tannic acid. The polymer has good flexibility and strength, which is conducive to alleviating the volume expansion of the silicon material.

[0062] In some embodiments, the carbon material includes at least one of an amorphous carbon material and a graphitized carbon material. The carbon material has excellent electrical conductivity and can improve the electrical conductivity of the negative electrode material.

[0063] In some embodiments, the metal oxide includes at least one of oxides of Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca and Zn. The metal oxide has good mechanical strength and can improve the structural strength of the coating layer, thereby improving the structural strength of the negative electrode material particles.

[0064] In some embodiments, the phosphate includes at least one of magnesium phosphate, calcium phosphate, aluminum phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate and lanthanum phosphate. Phosphates have good electrical conductivity and low cost, and can improve the conductivity of negative electrode materials.

[0065] In some embodiments, the specific surface area of ​​the negative electrode material is 2 m 2 / g ~20 m 2 / g. Specifically, it can be 2m 2 / g, 3m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 15m 2 / g, 16m 2 / g, 18m 2 / g or 20m 2 / g, etc., are not limited here; it can be understood that the specific surface area of ​​the negative electrode material will affect the contact area between the negative electrode material and the electrolyte. The specific surface area of ​​the negative electrode material within the above range can reduce the amount of lithium ions consumed by the SEI film formed during the initial charge and discharge process of the lithium-ion battery, thereby reducing the irreversible capacity loss of the lithium-ion battery.

[0066] In some embodiments, the compacted density of the negative electrode material is 1.0 g / cm 3 ~1.8 g / cm 3 Specific examples include 1.0 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 or 1.8 g / cm 3 The compaction density of the negative electrode material is controlled within the above range, which is beneficial to improving the energy density of the negative electrode material.

[0067] In some embodiments, the powder conductivity of the negative electrode material is 0.5 S / cm~5 S / cm, specifically 0.5S / cm, 0.8S / cm, 1.0S / cm, 1.5S / cm, 1.8S / cm, 2.0S / cm, 2.5S / cm, 3.2S / cm, 4.0S / cm, 4.5S / cm or 5S / cm, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Due to the presence of metal nanoparticles and metal nanowires, the powder conductivity of the negative electrode material can be effectively improved. Preferably, the powder conductivity of the negative electrode material is 3.0 S / cm~5 S / cm.

[0068] In some embodiments, the mass percentage of carbon element in the negative electrode material is 19% to 39%, specifically 19%, 20%, 25%, 28%, 30%, 35%, 38% or 39%, etc., which is not limited here.

[0069] In some embodiments, the mass percentage of silicon in the negative electrode material is 60% to 80%. Specifically, it can be 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78% or 80%, etc., which are not limited here. It can be understood that controlling the mass percentage of silicon within the above range can increase the specific capacity of the negative electrode material and control the volume expansion of the negative electrode material.

[0070] In some embodiments, the gas production value of the negative electrode material is ≤15 mL / kg / day, which can be 15 mL / kg / day, 14 mL / kg / day, 12 mL / kg / day, 10 mL / kg / day, 8 mL / kg / day, 5 mL / kg / day, 3 mL / kg / day, 1 mL / kg / day or 0.1 mL / kg / day, etc., and of course, it can also be other values ​​within the above range, which is not limited here. The gas production value of the negative electrode material of the present application is controlled within the above range, which shows that most of the silicon particles can be relatively evenly distributed in the pores of the carbon matrix, thereby reducing the direct contact between the silicon particles and the electrolyte, thereby reducing the side reaction of the dissolved silicon particles and the electrolyte, and can also effectively reduce the gas production value of the negative electrode material.

[0071] The present application also provides a method for preparing a negative electrode material, such as Figure 2 As shown, the method includes the following steps S10~S30:

[0072] S10, adding the porous silicon material into a metal ion solution and performing a hydrothermal treatment to obtain a composite material;

[0073] S20, adding an impregnation solution containing a liquid carbon source and a metal ion solution to the composite material under negative pressure, heating and applying pressure to perform an impregnation treatment to obtain a precursor;

[0074] S30, in a reducing atmosphere, coating the precursor with a coating material to obtain a negative electrode material.

[0075] The preparation method of the negative electrode material provided in the present application first adds a porous silicon material to a metal ion mixed solution for hydrothermal treatment to obtain a composite material, the composite material includes a linear metal hydroxide and a porous silicon material, the linear metal hydroxide is at least partially distributed on the surface of the porous silicon material, and extends in a direction away from the porous silicon surface. Under a negative pressure state, an impregnation solution containing a liquid carbon source and a metal ion solution is added to the composite material, and the composite material is heated and pressure is applied for impregnation treatment. During the heating and impregnation treatment, the pores of the composite material are filled with the impregnation solution, and part of the impregnation solution will cover the surface of the porous silicon material. The precursor includes a composite material and a filler, and the filler includes a carbon source and metal hydroxide nanoparticles. The filler is at least partially located in the pores of the porous silicon, and part of the carbon source is distributed on at least part of the surface of the porous silicon. Finally, during the coating process, the carbon source impregnation liquid inside the silicon material is carbonized into carbon material, the metal hydroxide nanoparticles inside the silicon material are reduced to form metal nanoparticles, the carbon source impregnation liquid on the surface of the silicon material is carbonized to form a carbon layer, and the linear metal hydroxide on the surface of the silicon material is reduced to form metal nanowires. Some metal nanowires are staggered in the carbon layer, which can improve the mechanical strength and electronic conductivity of the carbon layer, thereby inhibiting the volume expansion of the silicon material and reducing the particle breakage and pulverization of the negative electrode material. Another part of the metal nanowires extends from the surface of the silicon material to the coating layer in a direction away from the surface of the silicon material, so that the electronic conductivity between the silicon material and the coating layer can be enhanced by the metal nanowires, and the powder conductivity of the negative electrode material can be improved. The coating layer formed after the coating treatment can cooperate with the carbon layer to effectively alleviate the volume expansion of the silicon material and ensure that the negative electrode material still has excellent electrical contact performance after lithium insertion. The coating layer can also effectively reduce the side reactions between the silicon material and the electrolyte, while enhancing the structural stability of the negative electrode material.

[0076] The method for preparing the negative electrode material provided in the present application can not only improve the electrochemical properties of the material, but also be suitable for large-scale production. The prepared negative electrode material can effectively improve the rate performance and cycle stability of the lithium battery.

[0077] The preparation method of the present application is described in detail below with reference to the examples:

[0078] Step S10, adding the porous silicon material into the metal ion solution and performing hydrothermal treatment to obtain a composite material.

[0079] In some embodiments, the porous silicon material is a primary particle, and the porous silicon material has pores inside.

[0080] In some embodiments, the pores of the porous silicon material include macropores and mesopores. According to the definition of the International Union of Pure and Applied Chemistry (IUPAC), pores with a pore size of >50 nm are called macropores, and pores with a pore size of 2 nm to 50 nm are called mesopores.

[0081] In some embodiments, the average pore size of the pores is 10 nm to 30 nm, indicating that most of the pores are mesopores. The three-dimensional pores distributed in the porous silicon material can alleviate the volume expansion of the silicon material during the lithium insertion process and provide internal expansion space for the lithiation reaction.

[0082] In some embodiments, the average particle size of the porous silicon material is 1 μm to 15 μm, and may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 11 μm, 13 μm, 14 μm or 15 μm, etc., which is not limited here.

[0083] In some embodiments, the porosity of the porous silicon material is 20% to 60%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc., which are not limited here. The suitable porosity of the silicon material can buffer the volume expansion of the silicon material during the lithium insertion process.

[0084] In some embodiments, the specific surface area of ​​the porous silicon material is 5 m 2 / g~400 m 2 / g, specifically 5 m 2 / g, 8m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 30m 2 / g, 50m 2 / g, 80m 2 / g、100m 2 / g, 200m 2 / g or 400m 2 / g, etc., which are not limited here. The main reason why the specific surface area of ​​silicon material is relatively large is that silicon material has abundant pores. When the carbon material doped with metal nanoparticles is filled into the pores of silicon material, the specific surface area of ​​silicon material of the composite carbon material can be significantly reduced, thereby reducing the direct contact between silicon material and electrolyte and reducing the occurrence of side reactions between the material and electrolyte.

[0085] In some embodiments, the compacted density of the porous silicon material is 0.8 g / cm 3 ~1.5g / cm 3 , specifically 0.8g / cm 3 , 0.9g / cm3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 Etc., no limitation is made here.

[0086] In some embodiments, the tap density of the porous silicon material is 0.5 g / cm 3 ~ 0.8g / cm 3 , specifically 0.5g / cm 3 , 0.6g / cm 3 , 0.65g / cm 3 , 0.7g / cm 3 , 0.75 g / cm 3 , 0.79g / cm 3 , 0.8g / cm 3 Etc., no limitation is made here.

[0087] In some embodiments, the volume ratio of mesopores to macropores is (1-10): 1; specifically, it can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc., which are not limited here. It can be understood that by controlling the volume proportion of macropores in the pore structure, the volume expansion of the battery prepared by the negative electrode material during the lithium insertion process can be alleviated, and it is also beneficial to provide internal expansion space for the lithiation of the material.

[0088] In some embodiments, the metal ion concentration in the metal ion solution is 0.1 mol / L~2 mol / L, specifically 0.1 mol / L, 0.2mol / L, 0.5mol / L, 0.8mol / L, 1.0mol / L, 1.2mol / L, 1.5mol / L, 1.8mol / L or 2mol / L, etc., and of course it can also be other values ​​within the above range.

[0089] In some embodiments, the metal ions in the metal ion solution include at least one of copper ions and silver ions. Specifically, the solute in the metal ion solution includes at least one of copper sulfate, silver sulfate, copper nitrate, and silver nitrate.

[0090] In some embodiments, the solvent in the metal ion solution includes water and an organic solvent, wherein the organic solvent includes one or a mixture of two or more of ethanol, propanol, acetone and N-methylpyrrolidone, wherein the volume proportion of the organic solvent in the total solvent is 60%-90%.

[0091] In some embodiments, the temperature of the hydrothermal treatment is 80°C to 150°C, and the time of the hydrothermal treatment is 0.5h to 4h. The temperature can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, and the time can be 0.5h, 1h, 2h, 2.5h, 3h, 3.5h or 4h, and of course, it can be other values ​​within the above range, which are not limited here.

[0092] In some embodiments, the ratio of silicon material to metal ion solution is 100:(400~800) g / mL, specifically 100:400 g / mL, 100:500 g / mL, 100:600 g / mL, 100:700 g / mL or 100:800 g / mL, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0093] In some embodiments, the product after the hydrothermal treatment is subjected to vacuum drying to obtain a composite material, wherein the vacuum drying temperature is 60° C. to 80° C., and the vacuum drying only needs to remove the solvent in the hydrothermal product.

[0094] S20, under negative pressure, adding an impregnation solution containing a liquid carbon source and a metal ion solution to the composite material, heating and applying pressure to perform an impregnation treatment to obtain a precursor, the precursor comprising a composite material and a filler, the filler comprising a carbon source and metal nanoparticles.

[0095] In some embodiments, the vacuum degree of the negative pressure state is 50 Pa to 100 Pa, specifically 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa or 100 Pa, etc., and of course, other values ​​within the above range may also be used, which are not limited here. The appropriate vacuum degree is conducive to the impregnation solution containing the liquid carbon source and the metal ion solution to enter the pores of the silicon material, and then in the subsequent treatment, the carbon material doped with metal nanoparticles is formed to fill the pores of the silicon material.

[0096] In some embodiments, the impregnation solution includes a liquid carbon source and a metal ion solution, and the liquid carbon source includes at least one of asphalt and resin. The metal ion solution here is the same as the metal ion solution in step S10, and will not be described again.

[0097] In some embodiments, the volume proportion of the metal ion solution in the impregnation solution is 20% to 40%, specifically 20%, 25%, 30%, 35% or 40%, etc., and of course other values ​​within the above range are also possible, which are not limited here.

[0098] In some embodiments, the mass ratio of the silicon material to the impregnation liquid is 100:(50~200), specifically 100:50, 100:60, 100:70, 100:80, 100:100, 100:120, 100:150, 100:180, 100:200, etc., and of course, other values ​​within the above range may also be used, which are not limited here. The present application can adjust the thickness of the first layer by controlling the mass ratio of the silicon material to the impregnation liquid, so that the thickness of the overall coating layer of the negative electrode material is within a suitable range, which is beneficial to the lithium ion transmission of the negative electrode material and maintaining a low expansion rate.

[0099] In some embodiments, the heating temperature of the impregnation treatment is 200°C to 250°C, and the temperature can be specifically 200°C, 210°C, 220°C, 230°C, 235°C, 240°C or 250°C, etc. The time of the impregnation treatment is 0.5h to 2.0h, and the time can be specifically 0.5h, 0.8h, 1.0h, 1.2h, 1.5h, 1.8h or 2.0h, etc., and of course it can also be other values ​​within the above range, which is not limited here. The heating temperature is controlled within the above range, which is conducive to the carbon source impregnation liquid being fully softened to a liquid state, so that the pores of the silicon material can be fully filled with carbon material.

[0100] In some embodiments, the applied pressure is 2 Mpa to 6 Mpa, specifically 2 Mpa, 3 Mpa, 4 Mpa, 5 Mpa or 6 Mpa, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0101] In some embodiments, the product after the impregnation treatment is dried to obtain a precursor. The purpose of drying is to remove the residual solvent in the product after the impregnation treatment.

[0102] S30, coating the precursor with a coating material in a reducing atmosphere to obtain a negative electrode material.

[0103] In some embodiments, the coating material includes at least one of a carbon material, a nitrogen material, a polymer, a metal oxide, and a phosphate.

[0104] In some embodiments, the coating material includes a carbon material, and the coating process includes at least one of solid phase carbon coating, liquid phase carbon coating, and gas phase carbon coating.

[0105] In some embodiments, the coating treatment is gas-phase carbon coating, specifically comprising: introducing a reducing atmosphere into the precursor and heat treating it at 600°C to 800°C for 0.5h to 2h, then introducing a gas-phase carbon source and heating it until the gas-phase carbon source undergoes a thermal cracking reaction, so that the surface of the precursor is deposited to form a coating material, and the coating material includes at least one of an amorphous carbon material and a graphitized carbon material. The gas-phase carbon source includes at least one of acetylene, methane, toluene, cyclohexane, ethanol, ethylene, and propylene.

[0106] In some embodiments, the reducing atmosphere includes hydrogen, carbon monoxide, etc., which are not limited here.

[0107] In some embodiments, the concentration of the reducing atmosphere is 0.1 L / min to 1 L / min; specifically, it can be 0.1 L / min, 0.4 L / min, 0.6 L / min, 0.8 L / min, 1.0 L / min, etc., which is not limited here.

[0108] In some embodiments, the heating rate is 1°C / min to 20°C / min, specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min, 20°C / min. It can be understood that when the heating rate is controlled within the above range, the carbon coating can be effectively guaranteed, and the time for heating to the preset temperature range can be shortened.

[0109] In some embodiments, the temperature of the thermal cracking reaction is 600°C to 1000°C, specifically, the reaction temperature can be 600°C, 650°C, 700°C, 750°C, 800°C, 890°C, 900°C, 960°C or 1000°C. The inventors have found through multiple experiments that controlling the reaction temperature within 600°C to 1000°C can improve the reaction efficiency, so that a uniform carbon layer is formed on the surface of the precursor, and the carbon layer can be amorphous carbon. Preferably, the reaction temperature is 700°C to 900°C.

[0110] In some embodiments, the insulation time of the thermal cracking reaction is 1 h to 48 h; specifically, it can be 1 h, 4 h, 8 h, 12 h, 16 h, 24 h, 28 h, 32 h, 38 h or 48 h, which is not limited here.

[0111] In some embodiments, the concentration of the gaseous carbon source is 0.1 L / min~10 L / min; specifically, it can be 0.1 L / min, 0.4 L / min, 0.6 L / min, 0.8 L / min, 1.0 L / min, 2 L / min, 5 L / min, 6 L / min, 8 L / min, 9 L / min or 10 L / min, etc., which is not limited here.

[0112] In some embodiments, the step of coating the precursor with a coating material includes: spray drying a mixed coating liquid containing the precursor and the polymer.

[0113] In some embodiments, the solid content of the precursor in the mixed coating liquid is 5% to 50%, specifically 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., which is not limited here.

[0114] In some embodiments, the mixed coating fluid includes a polar solvent.

[0115] In some embodiments, the polar solvent includes at least one of water, anhydrous ethanol, methanol, and isopropanol.

[0116] In some embodiments, the mass ratio of the precursor to the polymer is 10:(0.1-5), specifically 10:0.1, 10:1, 10:2, 10:3, 10:4 or 10:5, which is not limited here.

[0117] In some embodiments, the drying temperature of spray drying is 60°C to 200°C, specifically 60°C, 80°C, 100°C, 120°C, 150°C, 180°C or 200°C.

[0118] In some embodiments, the polymer includes at least one of polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polydopamine, xanthan gum, polypyrrole, polythiophene, polyphenylene vinylene, polyaniline, polyacetylene, and tannic acid.

[0119] The embodiment of the present invention further provides a battery, Figure 3 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 3 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0120] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .

[0121] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.

[0122] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.

[0123] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O 4) 、LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0124] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.

[0125] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0126] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0127] Example 1

[0128] (1) A porous silicon material with an average particle size of 3 μm and a porosity of 30% was mixed with a 0.5 mol / L copper sulfate solution, wherein the solvent in the copper sulfate solution included 70% ethanol by volume, and the mass / volume ratio of the porous silicon material to the copper sulfate solution was 100 g / 500 ml. The mixed solution of porous silicon and copper sulfate was then transferred to a high-temperature and high-pressure reactor at a hydrothermal temperature of 120°C for 2 hours. After the hydrothermal reaction was completed, the composite material was vacuum dried to obtain.

[0129] (2) The composite material was evacuated to a vacuum degree of 50 Pa, and then an impregnation liquid was added for impregnation treatment. The mass ratio of the silicon material to the impregnation liquid was 100:100. The impregnation liquid included a copper sulfate solution and liquid asphalt. The volume proportion of the copper sulfate solution in the impregnation liquid was 20%. A pressure of 3 MPa was applied, the temperature was raised to 200°C, the impregnation treatment time was 1 hour, and the precursor was obtained after vacuum drying.

[0130] (3) The precursor was placed in a rotary furnace and then heated to 700°C at a heating rate of 10°C / min. Hydrogen was introduced at a flow rate of 0.5 L / min for 2 hours, and then propane was introduced at a flow rate of 0.8 L / min for 1.5 hours. After cooling to room temperature, the negative electrode material was finally obtained.

[0131] Embodiment 2 to Embodiment 19

[0132] According to the preparation process of Example 1, the process parameters in Table 1 were adjusted to obtain a negative electrode material.

[0133] Embodiment 20

[0134] The difference from Example 1 is:

[0135] (3) placing the precursor of step (2) in a rotary kiln, then heating to 700°C at a heating rate of 10°C / min, introducing 0.5L / min of hydrogen and keeping the temperature for 2 hours, and cooling to obtain a composite; dissolving the composite in a polyacrylic acid solution, wherein the mass ratio of the composite to polyacrylic acid is 10:1, and the solvent of the polyacrylic acid solution is water; stirring evenly, and then spray drying at 80°C to obtain a negative electrode material.

[0136] Embodiment 21

[0137] The difference from Example 1 is:

[0138] (3) The precursor of step (2) is placed in a rotary kiln, and then heated to 700°C at a heating rate of 10°C / min, and hydrogen is introduced at 0.5L / min for 2 hours. After cooling to room temperature, it is then dissolved in a titanium tetrachloride solution, stirred for 30 minutes and then filtered. After vacuum drying, it is placed in a box furnace at 700°C in an argon atmosphere for 2 hours to finally obtain a negative electrode material.

[0139] Embodiment 22

[0140] The difference from Example 1 is:

[0141] (3) The precursor of step (2) is placed in a rotary furnace, and then heated to 700°C at a heating rate of 10°C / min, and hydrogen gas is introduced at 0.5L / min for 2 hours. After cooling to room temperature, it is then dissolved in a nickel nitrate solution, stirred for 30 minutes, and then filtered. After vacuum drying, it is placed in a tubular furnace, and diammonium hydrogen phosphate is placed at the front end of the tubular furnace. The argon atmosphere is 700°C and kept warm for 2 hours to finally obtain a negative electrode material.

[0142] Table 1. Comparison of process parameters of embodiments and comparative examples

[0143]

[0144] Comparative Example 1

[0145] Different from Example 1,

[0146] Step (1) is not performed, and the porous silicon material is directly used to replace the composite material for the impregnation treatment of step (2).

[0147] Comparative Example 2

[0148] Different from Example 1,

[0149] Without performing step (2), the composite material directly performs step (3).

[0150] Comparative Example 3

[0151] A porous silicon material with an average particle size of 3 μm and a porosity of 30% was placed in a rotary furnace, then heated to 700°C at a heating rate of 10°C / min, and 0.5 L / min of hydrogen was introduced for 2 hours, followed by a propane flow rate of 0.8 L / min for 1.5 hours. After cooling to room temperature, the negative electrode material was finally obtained.

[0152] Performance Testing

[0153] 1. Physical and chemical properties test of negative electrode materials

[0154] 1) Test method for specific surface area of ​​negative electrode material:

[0155] The equipment used is the TriStar3000&3020 fully automatic specific surface and pore size analyzer from Micromeritics Inc. of the United States, which complies with the national standard GB / T 19587-2017. Under constant temperature and low temperature, the adsorption amount of gas on the solid surface at different relative pressures is measured, and then the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material.

[0156] 2) Test method for compaction density:

[0157] Using the American CARVER 4350.22 powder compaction density tester, a sample of specified mass m is placed in a mold and a pressure of 1.0T is applied. After maintaining the pressure for 30s, the pressure is removed to test its thickness and the compaction density is calculated.

[0158] 3) SEM test:

[0159] Scanning electron microscopy characterization was carried out on a S4800 field emission electron microscope from Hitachi, Japan, with an operating voltage of 200 kV, to observe the structure of the negative electrode material and to scale the thickness of the coating layer.

[0160] 4) Test method for powder conductivity:

[0161] The MCP-PD51 powder resistance test system of Mitsubishi Chemical of Japan was used to test the conductivity under the pressure point of 20KN, and the four-probe method was used to determine the volume resistivity of the sample. The instrument can measure the resistance of the powder, and then the computer automatically calculates the conductivity and resistivity of the powder.

[0162] 5) Gas production test:

[0163] Place 5g of negative electrode material in a sealed container, add deionized water until the remaining volume above the container is 60ml, seal the container, mix well, and store at room temperature for one day. After 24 hours, shake the container again to disperse the precipitate into the liquid. Open the lid of the container, use a hydrogen detector to detect the concentration of hydrogen, and convert it to cc / (kg•day).

[0164] 6) Test method for the mass content of metal elements in negative electrode materials:

[0165] The ICP method is used to test the content of metal elements in the material. Test method: 0.500g of negative electrode material is placed in a clean platinum crucible, and then calcined at 750℃ in a muffle furnace in an air atmosphere for 2 hours to completely remove the carbon element; the cooled calcined residue is fully reacted with 4mL HNO3 and 6mL HF mixed acid, and then the platinum crucible containing the solution is placed on a 350℃ hot plate until the solvent is completely evaporated; after the crucible is cooled, 6mL HCl is added, heated until the residue is completely dissolved, and the volume is fixed to a 100mL plastic volumetric flask; finally, the mass percentage of Cu and / or Ag in the material is tested using an ICP spectrometer (Agilent 5800VDV ICP-OES) M .

[0166] 7) Mass percentage of silicon in negative electrode material

[0167] Use Nanyang Xinyu SA2-9-17TP box-type atmosphere furnace: first place the negative electrode material in an oxygen atmosphere to burn, so that the silicon in the sample reacts to become silicon dioxide, and the carbon is burned and discharged as carbon dioxide. Then place the burning residue in a nitric acid solution to fully react and remove the metal. After washing the residue, dry and weigh it, and calculate the mass percentage of silicon m Si .

[0168] 8) Testing method for average particle size of silicon materials:

[0169] The average particle size of the particles was measured using an E3500 ion mill and an S4800 field emission electron microscope produced by Hitachi, Japan.

[0170] 9) Testing method of pore volume of silicon material:

[0171] The test was carried out using ASAP2460 equipment from Micromeritics, USA, and the pore volume V was calculated using the BJH Desorption cumulative volume of pores model in the pore diameter range of 17 Å~3000 Å.

[0172] Micromeretics ASAP 2460 was used for macropore and mesopore analysis. At liquid nitrogen temperature, the equilibrium adsorption of nitrogen on the surface of an object is related to its pore size and other characteristics. Combined with the law of the change of adsorption amount with relative pressure during adsorption, multiple models can be fitted to calculate the pore size. The report generated by the software uses density functional theory (abbreviated as DFT) method to calculate the pore size distribution, total pore volume and pore volume within a certain range.

[0173] 10) Test method for thickness of first layer and second layer:

[0174] The material was sectioned using an E3500 ion mill and an S4800 field emission electron microscope from Hitachi, Japan, and the thickness of the first and second layers of the particles was measured in the SEM.

[0175] 11) Size test method for metal nanoparticles and metal nanowires:

[0176] The material was sectioned using an E3500 ion grinder and an S4800 field emission electron microscope from Hitachi, Japan. The sizes of the metal nanoparticles and metal nanowires were measured in the SEM. The length and diameter of 5-10 metal nanowires were directly measured using a scale, and the average values ​​of the length and diameter were taken. The particle sizes of 5-10 metal nanoparticles were measured, and the average values ​​of the particle sizes were taken.

[0177] 12) Testing method for the mass percentage of metal nanoparticles and metal nanowires in the negative electrode material:

[0178] The negative electrode material was sectioned using an E3500 ion grinder and an S4800 field emission electron microscope from Hitachi, Japan. Ten target areas were randomly selected from the core silicon material of the negative electrode material in the SEM. Each target area consisted of two sub-areas A1 and A2, where A1 = L1*D, L1 is the distance from the surface of the negative electrode material to the surface of the silicon material, and A2 = L2*D, L2 is the distance from the surface of the silicon material to the center of the negative electrode material particle.

[0179] By scanning the target area with EDS, the mass percentage of the metal element in the target area A1 and the mass percentage of the metal element in the target area A2 are obtained, and the mass percentage of the metal nanoparticles in the negative electrode material and the mass percentage of the metal nanowires in the negative electrode material are calculated.

[0180] After the above tests, the negative electrode materials prepared in the embodiments and comparative examples have performance parameters as described in Table 2:

[0181] Table 2. Performance parameters of negative electrode materials

[0182]

[0183] 2. Electrochemical test:

[0184] The negative electrode material was prepared into a slurry with a binder (PAA) and carbon black (SP) in a ratio of 80:15:5, with the mass percentage of the binder to the solvent being 5:95. The mixed slurry was coated on a copper foil current collector, dried and pressed to obtain a negative electrode sheet. The button cells were assembled in an argon atmosphere glove box. The separator used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1), and the counter electrode used was a metal lithium sheet.

[0185] The battery was tested for discharge specific capacity on the Blue Power CT2001A battery testing system. The ratio of the discharge power in one hour to the battery capacity is the discharge specific capacity.

[0186] The battery was tested for its first coulombic efficiency on a Blue Power CT2001A battery test system with a charge and discharge current density of 0.1C. The first coulombic efficiency was measured and a 50-cycle test was performed with a charge and discharge current of 0.1C. After 50 cycles, the battery capacity after the cycle and the capacity retention rate after the cycle were calculated, as shown in Table 3.

[0187] Table 3. Parameter performance comparison of each battery

[0188]

[0189] According to the preparation process parameters and test data of Examples 1 to 20 of the present application, by adding silicon material to a metal ion mixed solution for hydrothermal treatment, firstly adding a porous silicon material to a metal ion mixed solution for hydrothermal treatment to obtain a composite material, the composite material includes a linear metal hydroxide and a porous silicon material, the linear metal hydroxide is at least partially distributed on the surface of the porous silicon material, and extends in a direction away from the porous silicon surface. Under a negative pressure state, an impregnation solution containing a liquid carbon source and a metal ion solution is added to the composite material, heated and pressure is applied for impregnation treatment, during the heating and impregnation treatment, the pores of the composite material are filled with the impregnation solution, and part of the impregnation solution will cover the surface of the porous silicon material, the precursor includes a composite material and a filler, the filler includes a carbon source and metal hydroxide nanoparticles, the filler is at least partially located in the pores of the porous silicon material, and part of the carbon source is distributed on at least part of the surface of the porous silicon. Finally, during the coating process, the carbon source impregnation liquid inside the silicon material is carbonized into carbon material, the metal hydroxide nanoparticles inside the silicon material are reduced to form metal nanoparticles, the carbon source impregnation liquid on the surface of the silicon material is carbonized to form a carbon layer, and the nanowire-shaped metal hydroxide is reduced to form metal nanowires. Some metal nanowires are staggered in the carbon layer, which can improve the mechanical strength and electronic conductivity of the carbon layer, thereby inhibiting the volume expansion of the silicon material and reducing the particle breakage and pulverization of the negative electrode material. Another part of the metal nanowires extends along the thickness direction of the carbon layer to the surface and coating layer of the silicon material, so that the electronic conductivity between the silicon material and the coating layer can be enhanced by the metal nanowires, and the powder conductivity of the negative electrode material can be improved.

[0190] The negative electrode materials prepared in the examples of the present application have excellent powder conductivity, high capacity and high first coulombic efficiency. Among them, the powder conductivity of the negative electrode material prepared in Example 6 can reach a maximum of 5.0S / cm, the capacity is 2160mAh / g, the first coulombic efficiency can reach 90.8%, and the gas production value of the negative electrode material is 8 mL / kg / day.

[0191] According to the test data of Examples 1 to 4, when the negative electrode material is prepared using metal ion solutions of different solutes, that is, copper sulfate solution and / or copper nitrate solution, the mass percentage of metal nanoparticles and the mass percentage of metal nanowires in the negative electrode material are relatively close, and the powder conductivity, capacity and first coulomb efficiency of the negative electrode material can be maintained at a relatively excellent level. Among them, the powder conductivity of the negative electrode material prepared using silver ion solution is better than that of copper ion solution. The test results of the negative electrode materials prepared in Examples 1, 3 and 4 show that the powder conductivity performance of the negative electrode material prepared using a mixed solution of copper sulfate solution and silver nitrate is less than that of silver nitrate solution, but greater than that of copper sulfate solution. This is because the conductivity of silver is better than that of copper, but in terms of production cost, the production cost of silver is higher.

[0192] According to the test results of Examples 7, 1, 5 and 6, as the concentration of the metal ion solution gradually increases from 0.1 moL / L to 2.0 moL / L, the mass percentage of the metal element in the prepared negative electrode material is also gradually increased. Correspondingly, the powder conductivity of the negative electrode material is also gradually increased. It can be seen that the mass percentage of the metal nanoparticles and metal nanowires in the negative electrode material has a greater influence on the powder conductivity of the negative electrode material, and the appropriate metal content has a significant effect on improving the powder conductivity performance of the negative electrode material.

[0193] According to the test results of Examples 1 and 8 to 10, when the same concentration of metal ion solution is added, as the amount of metal ion solution added increases, the powder conductivity of the negative electrode material gradually increases. However, when the ratio of silicon material to metal ion solution reaches 100 / 600 g / mL or more, the degree of improvement in the powder conductivity of the negative electrode material tends to be stable.

[0194] The test results of Examples 1 and 11-12 prove that, during the preparation process, the thickness of the first coating carbon layer on the surface of the silicon material can be adjusted by adjusting the mass ratio of the silicon material to the impregnation solution. As the thickness of the carbon layer increases, the powder conductivity of the negative electrode material also increases.

[0195] According to the test results of Examples 1 and 13-14, during the preparation process, the volume proportion of the metal ion solution in the impregnation solution is adjusted. As the volume proportion increases, the powder conductivity of the negative electrode material also increases. This is because the impregnation solution can further bring in more metal ions under pressure, thereby improving the powder conductivity, and the compaction density of the negative electrode material can also be further improved.

[0196] The test results of Examples 1 and 15 to 17 show that, during the preparation process, as the pressurization pressure of the impregnation solution increases, the mass percentage of the metal elements filled into the pores of the silicon material will also increase, the powder conductivity of the negative electrode material will also increase, and the compaction density of the negative electrode material can also be further improved.

[0197] According to the test results of Examples 1 and 18-19, during the preparation process, as the vacuum degree of the impregnating solution increases, the mass percentage of the metal elements filled into the pores of the silicon material will also increase, the powder conductivity of the negative electrode material will also increase, and the compaction density of the negative electrode material can also be further improved.

[0198] The test results of Examples 1 and 20 to 22 show that different coating materials have an effect on the powder conductivity of the negative electrode material during the preparation process. The metal oxide coating layer, polymer coating layer and phosphate coating layer can all improve the powder conductivity of the negative electrode material. Preferably, the coating layer is a carbon layer.

[0199] According to the results of Example 1 and Comparative Examples 1 to 3, the performance of the negative electrode material prepared by hydrothermal treatment and heating impregnation is better than that of the negative electrode material prepared without hydrothermal treatment and heating impregnation, and the performance of the material prepared by hydrothermal treatment and pressure impregnation is better than that of the negative electrode material prepared by hydrothermal treatment or heating impregnation only. This is because, after hydrothermal treatment, the surface of the silicon material can grow and extend a large number of nanowire-shaped metal hydroxides away from the silicon material; during the pressure impregnation process and the heating impregnation process, the pores of the composite material are filled with the carbon source impregnation liquid, and during the filling process, part of the metal hydroxide and / or metal ions also enter the pores of the composite material with the carbon source impregnation liquid; this increases the percentage of metal elements in the pores of the silicon material, improves the electronic conductivity inside the silicon material, and is conducive to the transmission of electrons during the charge and discharge process, and the carbon material filled in the pores can also play a buffering role, buffering the stress of silicon volume expansion.

Claims

1. A negative electrode material, characterized in that: The invention comprises a core and a coating layer located on at least a portion of the surface of the core, wherein the core comprises a silicon material and a filler, wherein the filler is distributed in the silicon material, wherein the filler comprises a carbon material and metal nanoparticles, and wherein the coating layer comprises a first layer and a second layer arranged in sequence, wherein the first layer is distributed on at least a portion of the surface of the core, wherein the first layer comprises a carbon layer and metal nanowires distributed on the carbon layer; wherein the second layer is distributed on at least a portion of the surface of the first layer, wherein at least a portion of the metal nanowires extend from the surface of the silicon material through the first layer into the second layer; wherein the metal nanoparticles and the metal nanowires are made of the same material, and the metal nanoparticles and the metal nanowires are made of at least one of copper and silver or an alloy of the two.

2. The negative electrode material according to claim 1, characterized in that At least a portion of the metal nanowires extends from the surface of the silicon material into the carbon layer.

3. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: 1) The average particle size of the metal nanoparticles is 1 nm to 10 nm; 2) The mass percentage of the metal nanoparticles in the negative electrode material is 0.1% to 1.0%.

4. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: 1) The mass percentage of the metal nanowires in the negative electrode material is 1.0% to 3.5%; 2) The average length of the metal nanowires is 100 nm to 400 nm; 3) The average diameter of the metal nanowires is 2nm~10nm.

5. The negative electrode material according to claim 1, characterized in that The thickness of the first layer is 50 nm to 500 nm; and / or the thickness of the second layer is 50 nm to 100 nm.

6. The negative electrode material according to claim 1, characterized in that The material of the second layer includes at least one of carbon material, polymer, metal oxide and phosphate.

7. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: 1) The specific surface area of ​​the negative electrode material is 2 m 2 / g ~20 m 2 / g; 2) The compaction density of the negative electrode material is 1.0 g / cm 3 ~1.8g / cm 3 ; 3) The powder conductivity of the negative electrode material is 0.5 S / cm~5 S / cm; 4) The mass percentage of carbon element in the negative electrode material is 19% to 39%; 5) The mass percentage of silicon in the negative electrode material is 60% to 80%; 6) The gas production value of the negative electrode material is ≤15 mL / kg / day.

8. A battery, characterized in that: Comprising the negative electrode material as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Double-shell-layer structure composite material, preparation method of double-shell-layer structure composite material, and lithium ion battery containing composite material

    CN108511719A

  • Multi-ion doped silicon-carbon composite material and preparation method thereof

    CN118507696A

  • KR20210118318A